Effect of Nitro Group on Inhibition of 1070 Aluminium by Benzoic Acid in Nitric Acid. - YADAV, P.N.S.; SINGH, A.K.; W ADHWANI, R. (Asian Journal of Chemistry, 2010)
Corrosion inhibition action of o-, m- and p-nitrobenzoic acid has been thoroughly studied at 30, 40 and 50°C using weight loss and potentiostatic techniques. Inhibition efficiency of nitrobenzoic acids increases with concentrations but decreases with rise in temperatures. It has been found that nitro group exhibits beneficial effect on the inhibitive efficiency of the inhibitors. In case of all the inibitors maximum inhibition efficiency has been observed at 0.5% concentration. Lower value of activation energy and heat of adsorption have been obtained at higher temperatures. Polarisation studies reveal that these compounds act as mixed inhibitors.